THE EFFECT OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE AND PERSONALITY ON FINANCIAL MANAGEMENT BEHAVIOR IN COFFEE MSMES IN ACEH PROVINCE - Ristati, Ristati; Zulham, Zulham; Sutriani, Sutriani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This research is very important to do because it is necessary to do an in-depth study by combining theoretical and field studies on the factors that influence the behavior of financial management in MSMEs to maximize their contribution in increasing economic potential. The specific purpose of this study was to determine the effect of financial knowledge, financial attitudes and personality on financial management behavior in coffee MSMEs in Aceh Province. This type of associative research is a research that asks the relationship between financial knowledge, financial attitudes, and personality. The technique used is descriptive statistical analysis with SPSS as a data processing tool. This study explains the relationship between financial knowledge, financial attitudes, and personality on financial management behavior in coffee MSMEs in Aceh province. The results of the study are expected that by knowing the relationship between financial knowledge, financial attitudes, personality to financial management behavior, it can improve financial management in MSMEs to be better and be able to become a solution for MSME actors in making financial decisions on the business they are running.The outputs in this study consist of SINTA 5 Accredited National Journal Publications and HKI.